The effect of PFAS exposure on glucolipid metabolism in children and adolescents: a meta-analysis - Zheng, Qingqing; Yan, Wu; Gao, Shenghu; Li, Xiaonan (Frontiers in Endocrinology, 2024)
Background Previous studies showed that per- and polyfluoroalkyl substances (PFAS), which are widely found in the environment, can disrupt endocrine homeostasis when they enter the human body. This meta-analysis aimed to evaluate current human epidemiological evidence on the relationship between PFAS exposure and glucolipid metabolism in childhood and adolescence. Methods We searched PubMed, Web of Science, Embase, and Cochrane Library databases, and identified population-based epidemiological studies related to PFAS and glucolipid metabolism indexes that were published before 30 December 2022. The heterogeneity of the included literature was assessed using the I-square (I2) test and statistics Q. Random-effects and fixed-effects models were used to combine the effect size. Subgroup analysis based on age and sex of the study participants was performed. A sensitivity analysis was used to evaluate the robustness and reliability of the combined results. Egger’s and Begg’s tests were used to analyze publication bias. Results A total of 12 studies were included in this analysis. There was a positive association between PFAS and TC (β = 1.110, 95% CI: 0.601, 1.610) and LDL (β = 1.900, 95% CI: 1.030, 2.770), and a negative association between PFAS and HOMA-IR in children and adolescents (β = −0.130, 95% CI: −0. 200, −0.059). PFOS was significant positive associated with TC (β = 8.22, 95% CI: 3.93, 12.51), LDL (β = (12.04, 95% CI: 5.08, 18.99), and HOMA-IR (β = −0.165, 95% CI: −0.292, −0.038). Subgroup analysis showed that exposure to PFAS in the adolescent group was positively associated with TC and LDL levels, and the relationship was stronger in females. Conclusion PFAS exposure is associated with glucolipid metabolism in children and adolescents. Among them, PFOS may play an important role. Recognition of environmental PFAS exposure is critical for stabilizing the glycolipid metabolism relationship during the growth and development of children and adolescents.